Cross‐Scale Seismic Anisotropy Analysis in Metamorphic Rocks From the COSC‐1 Borehole in the Scandinavian Caledonides. Issue 5 (15th May 2021) - Kästner, Felix; Pierdominici, Simona; Zappone, Alba; Morales, Luiz F. G.; Schleicher, Anja M.; Wilke, Franziska D. H.; Berndt, Christian
Abstract: Metamorphic and deformed rocks in thrust zones show particularly high seismic anisotropy causing challenges for seismic imaging and interpretation. A good example is the Seve Nappe Complex in central Sweden, an old exhumed orogenic thrust zone that is characterized by a strong but incoherent seismic reflectivity and considerable seismic anisotropy. However, only little is known about their origin in relation to composition and structural influences on measurements at different seismic scales. Here, we present a new integrative study of cross‐scale seismic anisotropy analyses combining mineralogical composition, microstructural analyses, and seismic laboratory experiments from the COSC‐1 borehole, which sampled a 2.5‐km‐deep section of metamorphic rocks deformed in an orogenic root now preserved in the Lower Seve Nappe. While there is strong crystallographic preferred orientation in most samples in general, variations in anisotropy depend mostly on bulk mineral composition and dominant core lithology as shown by a strong correlation between these. This relationship enables to identify three distinct seismic anisotropy facies providing a continuous anisotropy profile along the borehole. Moreover, comparison of laboratory seismic measurements and electron‐backscatter diffraction data reveals a strong scale dependence, which is more pronounced in the highly deformed, heterogeneous samples. This highlights the need for comprehensive cross‐validation of microscale anisotropy analyses with additional lithological data when integrating seismic anisotropy over seismic scales. Key Points: Integrated study of seismic anisotropy in metamorphic rocks from the COSC‐1 borehole in the Swedish Caledonides Macroscale anisotropy is driven by major mineral assemblage, while modeled anisotropy dependent on microscale heterogeneity Results enable to derive facies‐based anisotropy model from core lithology to be compared with field data